Leptin mediates improvements in cognitive function following treatment with infliximab in adults with bipolar depression. (October 2020) - Mansur, Rodrigo B.; Subramaniapillai, Mehala; Lee, Yena; Pan, Zihang; Carmona, Nicole E.; Shekotikhina, Margarita; Iacobucci, Michelle; Rodrigues, Nelson; Nasri, Flora; Rashidian, Houman; Rosenblat, Joshua D.; Brietzke, Elisa; et al.
Highlights: Infliximab decreases plasma levels of leptin in patients with bipolar depression. Infliximab's effects on leptin were moderated by changes in sTNFR2 levels. Reduction in leptin levels were associated with improvements in verbal memory. Changes in leptin were also associated with increases in global cortical volume. Abstract: A potential role for leptin in the pathophysiology of bipolar disorder (BD) has been proposed. We recently investigated the effects of the tumor necrosis factor-alpha (TNF-α) antagonist infliximab in individuals with bipolar depression. Leptin is known to interact with the TNF-α system. Herein, we aimed to explore infliximab's effects on leptin and its relationship with brain structure and function. Sixty adults with bipolar depression were enrolled in this randomized, double-blind, 12-week clinical trial of adjunctive infliximab (n = 29) and saline control (n = 31), which were administered intravenously at weeks 0, 2, and 6. Plasma concentrations of leptin, TNF-α and soluble TNF receptors (sTNFR) 1 and 2 were assessed at weeks 0, 2, 6, and 12. We observed a significant decrease in leptin levels in infliximab-treated patients, relative to placebo. Infliximab treatment also significantly reduced TNF-α and sTNFR2, but not sTNFR1 levels. Changes in sTNR2 levels at week 6 significantly determined changes in leptin at week 12 in infliximab-, but not placebo-treated participants. Improvements in verbal memory and increases in global cortical volume were associated with reduction in leptin levels in the treatment group. Mediation analysis indicated that cognitive improvement in infliximab-treated patients was mediated by reductions in leptin levels, which in its turn were determined by decreases in sTNR2 levels. In conclusion, infliximab treatment reduced plasma leptin levels in individuals with BD, through modulation of sTNFR2. Decreases in leptin signaling were associated with an increase in global cortical volume and better performance in a verbal memory task.